The effect of aboveground long-term low-dose ionizing radiation on soil microbial diversity and structure - Cheng, Feng; Huang, Xiaofei; Qin, Qingao; Chen, Zijian; Li, Fei; Song, Wenchen (Frontiers in Ecology and Evolution, 2023)
Studies investigating the diversity and structure of soil microbial systems in response to ionizing radiation are scarce. In particular, effects of long-term low-dose radiation is rarely studied because of its unique conditions. In this study, an area in Chengdu, China, which has been irradiated by the radionuclide thorium-232 for more than 10 years was investigated. Four groups of samples with absorbed dose rates ranging from 192.906±5.05 to 910.964±41.09 nGy/h were collected to analyze the compositional and functional changes of the soil microbial systems in the region. The diversity and structure of the soil microbial systems were determined using high-throughput sequencing. Long-term low-dose ionizing radiation had no significant effect on soil bacterial diversity, but had a great impact on fungal diversity. Long-term ionizing radiation strongly affected soil microbial community structure. Long-term low-dose ionizing radiation was shown to have a promoting effect on iron-oxidizing bacteria and ectomycorrhizal fungi and have an inhibiting effect on predatory or parasitic fungi, further affecting the soil C/N ratio. This study is of great reference significance for future research on the impact of long-term low-dose ionizing radiation on soil ecosystems.